Magnetic resonance imaging and spectroscopy of fat emulsions in the gastrointestinal tract - Hussein, Mahamoud Omar (2013)
The relationship between meal structure and composition can modulate gastrointestinal processing and the resulting sense of satiety. This applies also to the fat component of meals and particularly to the surface area available for digestion. The main hypothesis underpinning this thesis work was that fat emulsion droplet size has a profound effect on fat digestion and, in turn, on the gastrointestinal and satiety responses. To test this hypothesis two fat emulsion meal systems were used. They had exactly the same composition but a small (termed the Fine emulsion, with a droplet size of 400 nm) or a large (termed the Coarse emulsion, with a droplet size of 8 μm) emulsified fat droplet size. The two fat emulsion systems were manufactured and characterised using a range of bench techniques, in vitro digestion models and MRI techniques in vitro. The difference in microstructure caused different temporal creaming characteristics for the emulsions and different percentage hydrolysis profiles in a gastric digestion model in vitro. The Fine emulsion showed initial rapid hydrolysis whilst the Coarse emulsion showed an initial slow hydrolysis phase with the hydrolysis rate increasing at later stages. This indicated that there was indeed a droplet size effect on fat hydrolysis whereby the smaller droplet size with a larger surface area hydrolysed faster than a larger droplet size. The emulsions’ performance was finally tested in vivo in healthy volunteers using MRI in a series of pilot studies leading to a main physiological study. Creaming differences in the gastric lumen were addressed by redesigning the meals using a locust bean gum (LBG) thickener that made them stable throughout the gastric emptying process. A main three-way physiological and satiety study in healthy volunteers showed that a highly emulsified, intragastrically stable emulsion delayed gastric emptying, increased small bowel water content and reduced consumption of food at the end of the study day. Finally, magnetic resonance imaging, relaxometry and spectroscopy were further evaluated to assess fat emulsion parameters in vitro and in vivo in the gastric lumen. Main static magnetic field and droplet size effects on T2 relaxation times of the Fine and the Coarse emulsions were observed. There was reasonable correlation between m-DIXON and spectroscopy methods to quantify fat fraction both in vitro and in vivo. Differences in T2 relaxation times for different droplet sizes of 20% fat emulsions were detected in vitro. These changes were however difficult to separate from creaming effects in vivo with a view of drawing meaningful inferences on droplet sizes. The main conclusion from this work was that manipulating food microstructure especially intragastric stability and fat emulsion droplet size can influence human gastrointestinal physiology and satiety responses and that MRI and MRS provide unique non invasive insights into these processes. This improved knowledge could help designing foods with desired health-promoting characteristics which could help to fight the rising tide of obesity.